Cortisol/DHEA ratio and hippocampal volume: A pilot study in major depression and healthy controls - Jin, Rowen O.; Mason, Sara; Mellon, Synthia H.; Epel, Elissa S.; Reus, Victor I.; Mahan, Laura; Rosser, Rebecca L.; Hough, Christina M.; Burke, Heather M.; Mueller, Susanne G.; Wolkowitz, Owen M. (Psychoneuroendocrinology, 2016)
•Cortisol was not significantly correlated with HCV in MDDs or controls.•DHEA(S) was positively correlated with HCV in MDDs but not in controls.•Cortisol:DHEA(S) ratios were negatively correlated with HCV across MDDs and controls.•It was hypothesized that cortisol effects on HCV may be modulated by DHEA(S). Structural imaging studies investigating the relationship between hippocampal volume (HCV) and peripheral measures of glucocorticoids (GCs) have produced conflicting results in both normal populations and in individuals with MDD, raising the possibility of other modulating factors. In preclinical studies, dehydroepiandrosterone (DHEA) and its sulfate ester (DHEAS; together abbreviated, DHEA(S)) have been shown to antagonize the actions of GCs on the central nervous system. Therefore, considering the relationship of HCV to both of these hormones simultaneously may be important, although it has rarely been done in human populations. Using high-resolution magnetic resonance imaging (MRI), the present pilot study examined the relationship between morning serum cortisol, DHEA(S), and HCV in nineteen normal controls and eighteen unmedicated subjects with Major Depressive Disorder (MDD). Serum cortisol and DHEA(S) were not significantly correlated with HCV across all subjects (cortisol: r=−0.165, p=0.33; DHEA: r=0.164, p=0.35; DHEAS: r=0.211, p=0.22, respectively). However, the ratios of cortisol/DHEA(S) were significantly negatively correlated with HCV in combined group (Cortisol/DHEA: r=−0.461, p=0.005; Cortisol/DHEAS: r=−0.363, p=0.03). Significant or near-significant correlations were found between some hormonal measurements and HCV in the MDDs alone (DHEA: r=0.482, p=0.059; DHEAS: r=0.507, p=0.045; cort/DHEA: r=−0.589, p=0.02; cort/DHEAS: r=−0.424p=0.10), but not in the controls alone (DHEA: r=0.070, p=0.79; DHEAS: r=0.077, p=0.77; cort/DHEA: r=−0.427, p=0.09; cort/DHEAS: r=−0.331, p=0.19). However, Group (MDDs vs controls) did not have a significant effect on the relationship between cortisol, DHEA(S), and their ratios with HCV (p>0.475 in all analyses). Although the exact relationship between serum and central steroid concentrations as well as their effects on the human hippocampus remains not known, these preliminary results suggest that the ratio of cortisol to DHEA(S), compared to serum cortisol alone, may convey additional information about “net steroid activity” with relation to HCV.